Cardiac implantable electronic devices in Bulgaria: results from the electronic registry BG-Pace for 2022 - V. Traykov; Sv. Iovev; B. Borisov; M. Marinov; V. Velchev; K. Dzhinsov (Българска кардиология, 2023)
The current study analyses the activity on cardiac pacing in Bulgaria in 2022 based on data derived from a national registry of patients with cardiac implantable electronic devices (CIEDs). Materials and methods. Data from the national registry BG-Pace for 2022 was studied retrospectively. Demographic data, procedure and device type, pacing mode, etiology, symptoms, preimplantation ECG, number of implantations, and centre and operator volumes were analyzed. Results: Four thousand seven hundred seventy devices were implanted by 45 operators in 30 centers. Median age was 76 (IQR 69-82, 14-98) years, and male patients were 2843 (59,6%). The most significant number of implantations were carried out in the age group 70-79 years. The most commonly implanted CIEDs were antibradycardia devices - 578,8/million. Of them, conduction system pacing was used in 111 (2.3%). Implanted cardioverter-defibrillators demonstrated a growth compared to previous periods and reached 31.9/million. Cardiac resynchronization defibrillators implantations also shown a growth to 15.9/million. A considerable increase was found with implantable loop-recorders, which reached 8.8/million. Number of implantations per center was 115.5 (IQR 53-261.,3, 3-546), and 76,5 (IQR 36,8-154,8, 3-364) devices per operator. Dual chamber devices were most commonly implanted with a share of 83.1% in AVB I and II degrees, 72.5% in complete AVB, 82.6% in intraventricular conduction disturbances, and in 66.8% in patients with sick sinus syndrome. Pacing modes allowing for atrial sensing were most frequently implanted – 62.4% of all implantations for conduction disturbances. There was a significant increase in the use of VVI mode with increasing age (P<0.001). Conclusion: The national registry BG-Pace includes systematic clinical, demographical, and procedural data for CIED implantations in Bulgaria. There is a growth in the implantation rates compared to previous periods, but they remain lower than the average number for Europe.